2012
DOI: 10.1245/s10434-012-2306-6
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Parathyroid Cancer

Abstract: This study confirms the validity of both classification systems for disease outcome in patients with parathyroid cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 28 publications
1
40
0
4
Order By: Relevance
“…The low-risk group was stratified based on the finding of an infiltrative growth pattern with capsular invasion and surrounding soft tissue invasion. The high-risk group showed evidence of vascular invasion with or without invasion of vital organs or distant metastases [74]. The highrisk group had a 12.8 times higher rate of recurrence and a considerably lower 5-year disease-free survival compared to the low-risk group.…”
Section: Stagingmentioning
confidence: 88%
“…The low-risk group was stratified based on the finding of an infiltrative growth pattern with capsular invasion and surrounding soft tissue invasion. The high-risk group showed evidence of vascular invasion with or without invasion of vital organs or distant metastases [74]. The highrisk group had a 12.8 times higher rate of recurrence and a considerably lower 5-year disease-free survival compared to the low-risk group.…”
Section: Stagingmentioning
confidence: 88%
“…The only classification criteria are those proposed by Schulte et al, in which the cut-off between low-risk and high-risk cancers is defined from the lymph node metastases and the involvement of the major anatomical neck structures, such as trachea, oesophagus and major neck vessels (26). Although several diagnostic exams have been proposed for the diagnosis of the PC, neck ultrasound is the most reliable for the initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term follow-up and information on mortality are not available, but the advanced stage of the PC at diagnosis likely predict a poor prognosis, worse than that of patients with classical hypercalcemic PC (2,7,9,(49)(50)(51)(52)(53). In the present case, we preferred to perform a thyroid lobectomy because of the pre-existent ipsi-lateral vocal fold paralysis and for taking the opportunity of avoiding the possible sequelae and complications of the total thyroidectomy (57)(58)(59)).…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…Schulte reported that the low-risk (invasion limited to the capsule and soft tissue) versus high-risk (vascular invasion, lymph node metastasis or invasion of the trachea, esophagus or major cervical vessels) classification was an excellent predictor of disease-specific mortality and recurrence in a multicenter validation study on parathyroid carcinoma. 41 Using the information provided by various reviews on parathyroid carcinoma, Shaha and Shah proposed a staging system based on the size of the tumor, extent of local invasion, and presence of regional nodal disease and distant metastasis. 42 Ultrasonography, radionuclide scanning, computed tomography (CT) and magnetic resonance imaging (MRI) have been used for the initial diagnosis and the detection of recurrence in patients with parathyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%